2006
DOI: 10.1021/ma061124k
|View full text |Cite
|
Sign up to set email alerts
|

Syndiotactic Polystyrene Physical Gels:  Guest Influence on Structural Order in Molecular Complex Domains and Gel Transparency

Abstract: Correlation lengths of crystalline domains of syndiotactic polystyrene (sPS) gels prepared in different solvents, and those of derived aerogels, have been investigated by wide-angle X-ray diffraction. The correlation length (D 010), along the direction perpendicular to the ac layers of close-packed enantiomorphous s(2/1)2 helices, is strongly dependent on the chemical nature of the guest molecules not only for molecular complex phases of gels but also for the nanoporous crystalline δ phase of aerogels. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 31 publications
(28 reference statements)
4
36
0
Order By: Relevance
“…For example, Hou et al reported ES block copolymer having 56–87 mol % of styrene with melting points of 214–245 °C 19 and Grassi and coworkers reported melting temperatures of 200–242 °C for sPS‐ block ‐PE copolymers (43–93 mol % styrene) prepared by hydrogenation of syndiotactic styrene‐butadiene block copolymers 51. Thus, although the data from this work and that of Yokota23 are consistent with blocky sPS/ES copolymers derived from B (or its tetramethyl analogue), the similar solubility of ES copolymers and low‐melting sPS in THF and the well‐known ability of sPS to form clathrates and gels52 illustrate the challenges of distinguishing sPS/ES block copolymers from their blends.…”
Section: Resultssupporting
confidence: 63%
“…For example, Hou et al reported ES block copolymer having 56–87 mol % of styrene with melting points of 214–245 °C 19 and Grassi and coworkers reported melting temperatures of 200–242 °C for sPS‐ block ‐PE copolymers (43–93 mol % styrene) prepared by hydrogenation of syndiotactic styrene‐butadiene block copolymers 51. Thus, although the data from this work and that of Yokota23 are consistent with blocky sPS/ES copolymers derived from B (or its tetramethyl analogue), the similar solubility of ES copolymers and low‐melting sPS in THF and the well‐known ability of sPS to form clathrates and gels52 illustrate the challenges of distinguishing sPS/ES block copolymers from their blends.…”
Section: Resultssupporting
confidence: 63%
“…The average crystalline size was calculated by the Scherrer formula:43, 44 where L hkl is the crystalline domain size (nm), λ is 0.1542 nm, and θ is the diffraction angle (rad). L hkl was considered as an average dimension perpendicular to the reflecting planes ( hkl ).…”
Section: Resultsmentioning
confidence: 99%
“…where I 300 is the intensity of the b-phase reflection, which was located at 2y % 16.0 , and I 110 , I 040 , and I 130 are the intensities of the corresponding monoclinic diffraction peaks. The average crystalline size was calculated by the Scherrer formula: 43,44…”
Section: Crystal Structures Of Pp and Its Nanocompositesmentioning
confidence: 99%
“…Dried gels for X‐ray diffraction measurements were prepared from the slowly‐crystallized as‐prepared gels by supercritical drying using a CO 2 critical‐point dryer (SPI Supplies). This method generally allows for interface‐free removal of the solvent, thereby preventing the collapse of the swollen as‐prepared gel due to the absence of surface tension and resulting in minimal associated changes to the microstructure of the polymer‐rich phase . The sealed DSC crucibles containing the gel samples were opened and immediately flushed with liquid CO 2 at ∼15 °C; the samples were then left for 2 h allowing solvent exchange to take place.…”
Section: Methodsmentioning
confidence: 99%